Structural analysis of horizontal axis tidal turbine (HATT) blade with varying material and laminate structures - Uy, Glizelda L.
The blades of a horizontal axis tidal turbine (HATT) are the key structural components that are decisive for the efficient conversion of the kinetic energy of the inflowing tidal current flow into mechanical torque that is converted into electrical energy in the generator of a tidal turbine. During its operations, tidal turbine blades are subjected to significant hydrodynamic forces due to the high density of the seawater in which they operate. These thrust loadings lead to high stresses and deflections at the blade, which can prove to be a serious design constraint for HATTs and can have implications with respect to the effectiveness and efficiency of the tidal turbine system. In this study, a structural performance analysis of a HATT blade model was assessed and the effects of the [15]s, [30]s, [45]s, [60]s, [75]s, [0/90]s ply laminate orientations on the structural integrity of the blade were investigated. A HATT blade model is designed and analyzed using Finite Element Modeling in ANSYS and the Blade Element Momentum Theory (BEM) was used to generate the blade forces data in QBlade. Composite materials for HATT Blade such as the Glass Fiber-Reinforced Composite and Carbon Fiber-Reinforced Composite with balanced symmetric laminates of standard ply angle orientations structures are considered to determine the appropriate configurations that will yield the least blade tip deflection with low principal stress. Results from the FEA static structural analysis in ANSYS showed that the ply laminate configuration of the Carbon Fiber-Reinforced Composite ply laminate [75]s exhibits the lowest blade tip deflection of 78.493 mm and low principal stress of 217.51 MPa. This ply laminate has highest potential among all the studied ply laminates for a good HATT hydroperformance and effective for a high structural reliability with minimal blade deflections and stress at average tidal current flow conditions.